Combination of catalytic ozonation by regenerated granular activated carbon (rGAC) and biological activated carbon in the advanced treatment of textile wastewater for reclamation. (September 2019) - Wang, Wen-Long; Hu, Hong-Ying; Liu, Xin; Shi, Hui-Xiang; Zhou, Tian-Hui; Wang, Chun; Huo, Zheng-Yang; Wu, Qian-Yuan
Abstract: Wastewater reclamation in the textile industry has attracted considerable attention. In this study, catalytic ozonation by regenerated granular activated carbon (rGAC) and its combination with biological activated carbon (BAC) was investigated for the reclamation of a real bio-treated dyeing and finishing wastewater (BDFW). Catalytic ozonation by rGAC (O3 /rGAC) was 1.6–2.0 times more efficient than ozonation alone for pollutants degradation. Although iron oxide loaded rGAC (rGAC-Fe) improved the performance of catalytic ozonation by 14%–25%, but was labile (<2 days) compared to stable rGAC (>20 days). Catalytic ozonation improved the generation of OH, contributing 1.1–1.7 times faster of chromophores decomposition and 0.24–0.55 times more increase of biodegradability than ozonation. However, catalytic ozonation increased the acute toxicity of BDFW by two times. The combination of O3 /rGAC and BAC can synergistically reduce COD, chromophores, and color in BDFW during 45-day's continuous operation, the improvements than O3 /rGAC being 21.0%, 18.8%, and 13.6%, respectively. Moreover, although O3 /rGAC of BDFW increased the toxicity from 98.3 to 146.5 μg-HgCl2 /L, post BAC significantly reduced the toxicity to 13.1 μg-HgCl2 /L. Engineering practice of water reclamation by O3 /rGAC-BAC was approved to be feasible based on both the water quality of treated water and the operation cost. Graphical abstract: Image 1 Highlights: Regenerated GAC (rGAC) was efficient and stable for catalytic ozonation. O3 /rGAC was 1.6–2 times as efficient as O3 for biotreated textile wastewater. OH generated by rGAC and rGAC-Fe contributed 55–65% to chromophore degradation. O3 /rGAC converted more recalcitrant chromophore to biodegradable product than O3 . O3 /rGAC and BAC work synergistically for pollutants degradation and detoxification.